The generation of dual purpose wheat that is high yielding, adapted to climate change and provides straw that is specifically adapted for bio-refining - Waldron, Paul (2017)
The planet we live on is for all intents and purposes a closed environment with finite resources, which over the last few hundred years humans have managed to deplete at an alarming rate. As they take millions of years to form they will eventual run out, and because of this there is a clear need for a sustainable replacement for liquid fossil fuels. Wheat straw is an agricultural waste product that has the potential to produce 70 gallons of ethanol per ton of biomass. The aim of this work was to firstly identify variation in wheat straw tissue and growing conditions with regard to recalcitrance and sugar availability for bio-fuel production; this was carried out using the commercial wheat variety Xi19. Xi19 was fractionated into leaf, peduncle- both upper (stem above 10cm) and lower (stem below 10cm) fractions, and samples of “whole” un-fractionated straw. It was found that the only differences seen with regard to tissue type was between the leaf samples and all other fractions (p < 0.05). Xi19, Cordiale and Grafton grown in field conditions under differing plant growth regulator (PGR) and nitrogen applications were then analysed using leaf, stem and “whole” un-fractionated straw and it was shown that neither treatment had any significant impact on recalcitrance and sugar availability (p > 0.05).